Small and Medium Business - Accelerator of Labor Market - Bartkus, Edverdas (Ekonomika, 2004)
Methodological problems of evaluation of small and medium business (SMB) development are analyzed in the article. Special attention is devoted to defining the importance of small and medium business in the economy system; and its position in Lithuania is analyzed in detail. The main attention is paid to the contribution of small and medium business when establishing general surplus value; and to evaluation of the employees employed in this economic sector, the number of small and medium businesses, and the results of their economic activity. This has allowed to form a rather clear view which preconditions will decide the development tendencies of small and medium business when Lithuania will be integrating into EU economic system.SMB development in Lithuania is becoming more and more important in the policy of Lithuanian Republic and in concrete actions which are going to be undertaken implementing state long-term development strategy and medium development strategic directions of SMB in 2004.Macroeconomic indexes show that after 1999 recession economics in this country is growing and developing quickly. SMB policy can not only influence changes in macroeconomic indexes positively, but also it can influence employment. Therefore, it can influence buying potential of inhabitants - weak potential nowadays has been one of the main obstacles in internal consumption.Perspectives of SMBE activity will not only depend on the policy of the government of Lithuanian Republic, effectiveness of implementing means, ability to take and implement the practical experience of EU countries administrating instruments that could ensure progress in SMBE; but also on the activity and will of SMBE using means for encouraging SMB development.Enterprises in our country are becoming more resistant to various market challenges. Experiencing the critical situation some enterprises retreated from the market while others reorganized their manufacture and activity, acquired features to search for new markets, to adjust to changing conditions of activities.In recent years state institutions at last acknowledged the idea that you cannot doubt about the importance of small and medium business development in the social economic development of the country, however small and medium business development is not possible without the support from the state. The problems of activities and development of SMBE and the ways of their solution differ greatly from these characteristic to large enterprises. Therefore we mast encouraged the governments of different states, especially those that act during transitional periods from state planned regulation to the system of market economy, to establish the organizations for support of small and medium business which are initiated by the state. Their destination should be supplying the financial, technical, organizational-management support to small and medium business enterprises.Up to the year of 2004 of the government of Lithuanian Republic the following aims are foreseen in the sphere of SMB development:• to ensure the priority development of small and medium business sector;• to encourage the integration of small and medium business sector into the economic space of European Union;• to increase the competitiveness of small and medium business enterprises creating conditions to implement innovations and to use new technologies;• to encourage international cooperation, the increase of production and service export of small and medium business enterprises;• to finish the establishment of the main chains in the system of small and medium business sector development - institutional, informative and financial support infrastructure when implementing the strategy of small and medium business development.